PELATIHAN USAHA PEMBUATAN ROTI “NGAWI BAKERY” UNTUK MENINGKATKAN UMKM DI KELURAHAN SAGULUNG KOTA KECAMATAN SAGULUNG, KOTA BATAM - Megah, Suswanto Ismadi; Artanto , Tri; Sugiharti , Sri; Maileni , Dwi Afni (PUAN INDONESIA, 2025)
Abstract Small and medium enterprises managed by Mr. Parno, a 2nd grade elementary school graduate, are something extraordinary, because with a very minimal educational background but are able to provide jobs for many people. In this PKM activity, input is provided on how this UMKM business can grow rapidly. Home-based bread businesses that are managed by bringing the Brand Image from their hometown, namely Ngawi Regency, East Java, are able to compete in big cities like Batam. With the name "Ngawi Bakery". However, the obstacles experienced by the bread entrepreneur, Mr. Parno, for example, business capital to develop bread, by looking for credit cannot be done, but the presence of Community Service activities (PKM) from the University of Riau Islands provides input by making bread design banners, advertisements, and by sponsoring films made by academics from the University of Riau Islands (UNRIKA), in addition, halal permits and certification have also been made. The purpose of the community service activities carried out during the PKM period is to help the bread company "Ngawi Bakery" in expanding its marketing area by creating new marketing methods through social media and helping other marketing activities such as providing banners and involving local youth to participate in increasing sustainable economic activities. Thus, the Ngawi Bakery Bakery business can grow and help the economy of local residents by absorbing labor, thereby improving the economy of residents around the Sagulung Kota sub-district, Sagulung District, Batam City..